PRESENT DAY CONCERNS ON DIET OF PREGNANT AND NURSING MOTHERS - L.G. Mamonova ("Paediatrician" Publishers LLC, 2006)
Proper nutrition of women at pregnancy and delivery is known to provide basis for normal healthy growth and development of their children. Deficiency of animal proteins, vegetable fats, polyunsaturated fatty acids, vitamins (as b-carotine, А, Е, С, В2, В6, В12, folic acid), as well as calcium, magnesium, iron, cuprum, zinc, chrome, selenium, iodine and other microelements have been shown in the studies of actual diets of pregnant and nursing mothers in different regions of Russia, which was conducted by scientific research institute of nutrition, Russian academy of medical sciences. Methods of diet improvement to correct macro- and micronutrient deficiency in pregnant and nursing mothers, including use of specialized food products, are taken up in the article. Key words: diet, pregnant mothers, nursing mothers, nutritive support.